2016
DOI: 10.1038/jp.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Trial of labor after cesarean in the low-risk obstetric population: a retrospective nationwide cohort study

Abstract: Although these outcomes remain rare, low-risk women undergoing a TOL remain at increased risk of adverse maternal events as compared with those who chose elective repeat cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…However, significant heterogeneity was apparent among the mostly small single-center studies identified, and the AHRQ review regarded the strength of evidence on maternal infection overall to be low because of the variability in how infection was defined and because the evidence was considered to be indirect and to have a high risk of bias. Although a more recent population-based study conducted in the UK reported that the risk of severe maternal sepsis did not significantly differ with planned VBAC compared to ERCS [41], a large population-based study conducted in the US found an elevated risk of puerperal sepsis and major puerperal infection with planned VBAC [45], consistent with our overall findings. However, neither of these prior studies examined whether any associations were modified by prior vaginal delivery.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, significant heterogeneity was apparent among the mostly small single-center studies identified, and the AHRQ review regarded the strength of evidence on maternal infection overall to be low because of the variability in how infection was defined and because the evidence was considered to be indirect and to have a high risk of bias. Although a more recent population-based study conducted in the UK reported that the risk of severe maternal sepsis did not significantly differ with planned VBAC compared to ERCS [41], a large population-based study conducted in the US found an elevated risk of puerperal sepsis and major puerperal infection with planned VBAC [45], consistent with our overall findings. However, neither of these prior studies examined whether any associations were modified by prior vaginal delivery.…”
Section: Discussionsupporting
confidence: 89%
“…The AHRQ review [16] also found evidence that planned VBAC is associated with an increased risk of blood transfusion, but only when the meta-analysis was confined to the four identified studies of women delivered at term rather than any gestational age (pooled estimates: 0.7% for planned VBAC versus 0.5% for ERCS, RR 1.30, 95% CI 1.15–1.47). Since the AHRQ review, although a number of studies have found no significant difference in the risk of blood transfusion between women who had planned VBAC and those that had an ERCS [36,40,42,43], a few of the larger studies have reported an elevated risk of this outcome for planned VBAC [39,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In a low risk US population, New York state, 1998-2002, the TOLAC rate declined from 58.7% to 35.7% [19]. In Canada, a TOLAC rate of 21% has been reported in low risk pregnancies [20].…”
Section: Discussionmentioning
confidence: 98%
“…This finding suggests that the reduction in women undergoing TOLAC does not reflect improved selection of patients for VBAC [3,13]. Success rates for TOLAC range from 28 to 85% [3,[14][15][16] and are higher for women with a previous CS for nonrecurring indications, such as breech presentation, and for women with a previous vaginal birth [17][18][19][20]. Furthermore, TOLAC is supported by obstetrical best practice guidelines in numerous countries [7,9,11,21].…”
Section: Introductionmentioning
confidence: 99%